Methylene blue adsorption onto cockle shells-treated banana pith: optimization, isotherm, kinetic, and thermodynamic studies - Rosalyza, Hasan; Wong, Jie Ying; Chong, Chi Cheng; Nur Farhana, Jaafar; Rohayu, Jusoh; Aishah, Abdul Jalil; Herma Dina, Setiabudi (Department of Chemistry, Universitas Gadjah Mada Yogyakarta, 2020)
Two low-cost wastes, banana pith (BP) and cockle shells (CS) were explored towards methylene blue (MB) removal. The performance of cockle shells-treated banana pith (CS-BP) in MB removal was compared with untreated BP and commercially Ca(OH)2-treated BP (Ca(OH)2-BP). The adsorption efficacy was following the order of BP < CS-BP < Ca(OH)2-BP, indicating the positive role of alkaline treatment towards MB removal and great potential of CS as a low-cost activation material. The optimization of MB removal onto CS-BP was executed by response surface methodology (RSM) with three independent variables (adsorbent dosage (X1), initial pH (X2) and initial MB concentration (X3)), and the optimal condition was achieved at X1 = 1.17 g/L, X2 = pH 7 and X3 = 214 mg/L, with 87.32% of predicted MB removal. The experimental data well-fitted the pseudo-second-order kinetic (R2 > 0.99) and the Langmuir isotherm (R2 = 0.999) models, demonstrating the chemisorption and naturally homogeneous process. Thermodynamics study discovered that the MB removal by CS-BP is endothermic, feasible, spontaneous and randomness growth at a solid-solute interface. It is affirmed that CS could be employed as a low-cost activation material and CS-BP as a low-cost adsorbent.